Sundanese performing arts in the US as legacy of the Center for World Music - Foley, Kathy (UI Scholars Hub, 2025)
Presentation of Sundanese arts in the US by non-Sundanese grew from a program of the Center for World Music (CWM), an incubator for Sundanese performing arts practice in the San Francisco Bay area in the 1970s. Those (both Sundanese and American) coming out of that encounter engaged in intercultural teaching and performance of music, dance, and wayang (puppet/human dance theatre) in the US in the then developing programs leading to a BA or graduate degree in ethnomusicology, dance, or theatre arts. Performances by Sundanese gamelan groups with American artists in and beyond the university also developed. While such groups persist, socio-political shifts in Indonesia-US relations, including in West Java’s modernization and urbanization, more conservative interpretations of religion due to the post-1980s Islamic revival, and the ageing of teachers have impacted. At the same time, trends in American academia including the questioning of interculturalism as neocolonialism, the trends toward study of urban popular music, and changing American identity politics, caused shifts in the study and performance of Sundanese arts in the US.